Teacher Agency with Teacher Resilience in Facing Challenges in the Times Independent Curriculum Implementation - Annisa Satriani Dewi; Paulus Kuswandono (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
The implementation of Curiklum Merdeka, a new curriculum in Indonesia, has highlighted the importance of teacher agency and resilience. Curriculum changes and significant differences from the previous curriculum present challenges for Indonesian teachers, requiring the important role of teacher agency and resilience in identifying and solving problems effectively. The aim of this research is to see the correlation between teacher agency and their resilience when facing difficulties related to the implementation of the Merdeka Curriculum. This research uses a quantitative method strategy. 41 educators who have used the Merdeka Curriculum became research subjects. Participants were given closed-ended and open-ended questionnaires to complete to collect data. Semi-structured interviews were conducted to support the results of the questionnaire. For the questionnaire results, the researchers conducted descriptive statistical analysis with SPSS 26, and for the interview results, a narrative inquiry approach was used. This study found that teachers demonstrated a high level of agency and resilience in implementing the Merdeka Curriculum, using a variety of teaching methods and resources. There is a strong positive relationship between agency and teacher resilience, meaning that higher agency will increase resilience. However, teachers face challenges such as rigid mindsets, lack of preparation, limited resources, and technological difficulties.